Cryptic niche differentiation of novel sediment ecotypes of Ruegeria pomeroyi correlates with nitrate respiration. (28th December 2021) - Lin, Xingqin; McNichol, Jesse; Chu, Xiao; Qian, Yang; Luo, Haiwei
Summary: Marine intertidal sediments fluctuate in redox conditions and nutrient availability, and they are also known as an important sink of nitrogen mainly through denitrification, yet how denitrifying bacteria adapt to this dynamic habitat remains largely untapped. Here, we investigated novel intertidal benthic ecotypes of the model pelagic marine bacterium Ruegeria pomeroyi DSS‐3 with a population genomic approach. While differing by only 1.3% at the 16S rRNA gene level, members of the intertidal benthic ecotypes are complete denitrifiers whereas the pelagic ecotype representative (DSS‐3) is a partial denitrifier lacking a nitrate reductase. The intertidal benthic ecotypes are further differentiated by using non‐homologous nitrate reductases and a different set of genes that allow alleviating oxidative stress and acquiring organic substrates. In the presence of nitrate, the two ecotypes showed contrasting growth patterns under initial oxygen concentrations at 1 vol% versus 7 vol% and supplemented with different carbon sources abundant in intertidal sediments. Collectively, this combination of evidence indicates that there are cryptic niches in coastal intertidal sediments that support divergent evolution of denitrifying bacteria. This knowledge will in turn help understand how these benthic environments operate to effectively remove nitrogen.